Analgesic, Hypoglycemic and Antidiarrheal Activities Screening of Canna indica L. (Bangladesh Pharmaceutical Journal, 2022)
The rhizome of Canna indica L. (family: Cannaceae) was extracted in methanol and two doses- 200 and 400 mg/kg body weight of the extract were employed to reveal central and peripheral analgesic, hypoglycemic and antidiarrheal properties in vivo. According to tail immersion technique, both doses significantly rose the time of latent response for 90 minutes compared to control mice group in assessing central analgesia. Acetic acid-induced writhing process demonstrated 37.29% and 64.41% inhibition of mice movement at both doses, respectively which indicated promising and statistically significant peripheral analgesic effect. On the other hand, hypoglycemic and antidiarrheal activities maintained dose and time dependent manner. Moreover, the extract of rhizome displayed statistically significant antidiarrheal activity at 400 mg/kg b.w. dose.Bangladesh Pharmaceutical Journal 25(2): 137-142, 2022 (July)